Branching Fin Influence on Phase Transition and Hybrid Nanofluid Forced Convection in A Double Vented Heat Exchanger Unit Equipped with Encapsulated PCM and Field Reconstruction by Using POD - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Springer/Plenum Publishers, 2025)
Methods are needed to improve the effusiveness of using encapsulated phase change materials (PCMs) in thermo-fluid systems. In this study, effects of using branching fin on melt fraction of encapsulated PCM in a double vented cavity system which are separated by a thin partition is numerically explored during forced convection of ternary nanofluid. The study is carried out for different values of the Reynolds number (Re, between 200 and 1000), opening ratio (OR between 0.5 and 1.5), branching fin length (between 0.01H and 0.15H), and fin position (sf\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$s_{f}$$\end{document} between 0.15H and 0.3H) by using finite element method. The presence of the branching fin induces vortices near the fin while both thermal performance and melt dynamics are influenced. The increment and decrement amounts of the entire transition time (TR) from Re = 200 to Re = 600 and from Re = 600 to Re = 1000 are 30 % and 17 %, respectively. Improvements in thermal performance at the maximum Re of the left and right cavities are 35.3 % and 58.6 %, respectively. For maximum heat transfer, the optimum OR value is 1, while for minimal TR, it is 1.75. Reduction in the TR up to 30 % and thermal performance improvement up to 39 % can be achieved by varying branching fin length. The average Nu variations with fin placements and the complete transition time are determined to be 20 % and 49 %, respectively. Utilizing branching fins at the lowest Re case decreases TR by 21.9 %, however it is lowered to 41.5 % at Re = 1000 when the reference scenario without branching fin at Re = 200 is taken into account. Time-dependent spatial variation of liquids fraction in the triangular zone is reconstructed for different Re values by using proper orthogonal decomposition.
Keywords: Branching fin; Encapsulated PCM; FEM; POD; Triangular vented cavity; Ternary hybrid nanofluid